Application of Personalized Demand Based on Kano Model in Private Colleges - Youmei Qiu (Discrete Dynamics in Nature and Society)
In recent years, with the continuous growth of college students’ personalities, the development of their personalized education needs has become more and more prominent, and how to meet those needs has become the focus of current research. From the perspective of Kano, this paper establishes a “student-centered” learning situation analysis system, based on the degree of support for graduation requirements and the training objectives for the individual needs of students. Furthermore, the paper builds a trinity of individual needs-oriented education evaluation mode, so as to realize the basic needs, expected needs, and attractive needs of students, and forms a teaching implementation plan for personalized needs from the perspective of Kano. Then, the established teaching implementation plan of individual needs from the perspective of Kano is applied to the “applied statistics” course of economic management students in a private college, and the experimental results of the undergraduate students and the students who are promoted to college are compared. The research shows the following: the application of the teaching implementation plan of personalized needs from the perspective of Kano can help improve the comprehensive performance of students; differentiated students can reduce differences through the teaching implementation plan of personalized needs from the perspective of Kano, so that personalized needs are more satisfied, so as to further improve the quality of teaching.